Assessment of the Volatile Profiles and Identification of Differentiating Aromas of Wild Undervalued Plants - Fukalova Fukalova, Tamara; Moreno-Peris, Estela; García-Martínez, María Dolores; Raigón Jiménez, María Dolores (Frontiers in Nutrition, 2022)
Wild edible plants have played an important role in traditional diets, including the Mediterranean diet. Many of these plants have acquired an undervalued status, since they are under-appreciated in terms of their nutritional, organoleptic qualities, or their seasonality. However, some of these species are still used in local gastronomy for their aromatic and taste characteristics. This study has investigated the quantitative and qualitative aromatic characteristics of seven undervalued wild plants that determine their organoleptic characteristics. Volatiles of the fresh leaves of each species have been determined by head-space solid-phase microextraction, a sensitive and solvent-free technique, coupled with gas chromatography and mass spectrometry. A total of 37 compounds with remarkable quantitative and qualitative differences were identified. In general, benzenoids and monoterpenoids were the most abundant groups, while branched unsaturated hydrocarbons, fatty alcohols, and sesquiterpenoids were the minor groups. Benzyl nitrile, benzyl isothiocyanate, p-cymene, and 2-hexenal were the main individual volatiles, while benzyl alcohol, eugenol, and α-copaene were the differentiating aromas. The results display that the undervalued species studied could be a suitable choice to include as new environmentally friendly crops, providing a double benefit to producers, because they are a possible way to achieve sustainable production systems, and they are an alternative for consumers, because these plants provide flavors that have high organoleptic qualities.